Factors Influencing the Incidence of Diarrhea - Listina, Febria; Aziza, Nurul; Marsyah, Marsyah (Global Health Science Group, 2024)
Diarrhea remains a major cause of morbidity and mortality due to infections in infants and children worldwide. Diarrhea is responsible for one-third of child deaths, resulting in the loss of two million children per year. The aim of this study is to identify the factors influencing the incidence of diarrhea in the working area of Puskesmas Natar, South Lampung Regency. This is a quantitative study with a cross-sectional research design. The population in this study consists of mothers who have children under five years old experiencing diarrhea and are registered at Puskesmas Natar, South Lampung Regency, totaling 751 respondents. The sample size in this study is 88 respondents. The sampling technique used in this study is stratified random sampling. Based on statistical tests, the knowledge variable showed a p-value of 0.010 < 0.05 (OR = 3.095), indicating a relationship between knowledge and the incidence of diarrhea. The attitude variable showed a p- value of 0.041 < 0.05 (OR = 2.444). There is a relationship between knowledge, exclusive breastfeeding, and attitude with the incidence of diarrhea.